Penetrating abdominal injuries in children (2002)
Traumatic injuries are leading causes of morbidity and mortality in children. The ubiquity of various types of weaponry (which is culturally and geographically dependent) has created an epidemic of violence that is spreading into all walks of life, and affecting all ages. The abdomen is the third most commonly injured region in children; 20% of the abdominal injuries are of the penetrating variety, the small intestine being the most commonly injured organ. In this article two illustrative cases of penetrating abdominal injury (PAI), causes, mechanism and pathophysiology of PAI, resuscitation and evaluation are presented. Treatment options with particular reference to the four commonly injured viscera and experience are also discussed.